A non-emulative moment connection for progressive collapse resistance in precast concrete building frames. (15th January 2019) - Quiel, Spencer E.; Naito, Clay J.; Fallon, Corey T.
Highlights: Developed a moment connection for a progressive collapse resistant precast frame. Experimental destructive testing was performed to obtain moment-rotation behavior. 2 configurations were tested: higher strength with lower ductility and vice versa. Experimental results were input into a system-level computational model. Models show that both tested connections prevent collapse for a column removal. Abstract: This paper documents the experimental development of a new spandrel-to-column moment connection detail for progressive collapse resistance in precast concrete building frames. This study focuses on a 10-story prototype precast concrete frame building with perimeter special moment frames (SMF) that are subjected to a ground-floor column removal. The experimental subassembly represents a spandrel-to-column connection on the perimeter SMF near the middle of the building face (i.e. not at the corners). The connection is non-emulative and utilizes unbonded high-strength steel post-tensioning (PT) bars which pass through ducts in the column and are anchored to the spandrels via bearing plates. The proposed design strives for construction simplicity, avoids field welding and/or grouting, and maximizes ductility by allowing the high strength steel bars to act as structural "fuses" when yielding. A full-scale quasi-static pushdown test is performed on two variants of the proposed connection: one with higher moment-rotation capacity and limited ductility, and another with lower capacity and higher ductility. The results show that the connection can reliably achieve its design yield capacity, performs well under service level demands, and can achieve moderate-to-high ductility. The experimental results are then applied to a system-level computational model of the prototype building frame under a column removal scenario. The results of a nonlinear dynamic analysis demonstrate that the system can arrest progressive collapse in the event of a single column loss scenario when either variant of the proposed connection is considered.